The long march - Liu, John D. ([S.l.] : TVE (production company) ; [S.l.] : Journeyman Pictures, 2002)
An overview on how Chengdu, one of the provincial capital of South West China, solved it's water pollution problem.
Keywords: China -- Social life and customs